Effect of electronic medical record utilization on Depression, anxiety and stress among doctors and Nurses in johor - Mohamed, Ahmad Fairuz (2012)
Healthcare systems throughout the world and in Malaysia are transforming from industrial age healthcare system to information and communication age healthcare system. This transformation will support and strengthened by telemedicine. However, many doctors and nurses are facing with the challenges and obstacles of this implementation of electronic medical record. Thus, this study was designed to evaluate the effect of electronic medical record utilization on depression, anxiety and stress among doctors and nurses in Johor. A comparative cross-sectional study was conducted between January till April 2012 among doctors and nurses in Hospital Sultan Ismail, Johor Bharu (HSIJB) which using electronic medical record and Hospital Pakar Sultanah Fatimah, Muar (HPSF) using manual medical record. There were 130 respondents with response rate 91% for electronic medical record and 123 respondents with response rate 86% for manual medical record. Data was collected using self-administered questionnaire which consists of socio-demographic and occupational characteristics and validated Malay version of Depression, Anxiety, Stress Scales-21 items (DASS-21). The mean (SD) age of respondents electronic medical record and manual medical record group were 34.7 (9.42) and 29.7 (6.15). The mean (SD) duration of respondents using electronic medical record was 46.1 (35.83) months. The prevalence of depression, anxiety and stress among respondents using electronic medical record were 6.9%, 25.4% and 12.3%. There were no significance difference proportion of depression, anxiety and stress between respondents using electronic medical record and manual medical record. In multivariable analysis, the significant factors associated with depression among respondents using electronic medical record was age (OR 1.10, 95% CI 1.02,1.19). The significant factors associated with stress among respondents using EMR was marital status (OR 3.33, 95% CI 1.10,10.09) and borderline significant was computer skill course (OR 2.94, 95% CI 0.98,8.78). There was no significant factor associated with anxiety among respondents using electronic medical record. The prevalence of depression, anxiety and stress respondents using electronic medical record were within range of prevalence depression, anxiety and stress in Malaysia and worldwide. There were no different in mental health outcome among those doctors and nurses using electronic medical record compared to manual medical record. This reflects the successful of Telehealth projects in Malaysia by Ministry of Health and also may reflect the good coping mechanism. In this study, we were found that age was predicted factor for depression among respondents using electronic medical record. We also able to show that computer skill course and marital status were factors that associated with stress level among respondents using electronic medical record.